Pengaruh Model Pembelajaran Problem Based Learning (PBL) pada Materi Larutan Penyangga Terhadap Hasil Belajar Siswa Kelas XI IPA SMA Negeri 5 Model Palu - Indah Lestari Malahat; Ratman Ratman (Universitas Tadulako, 2022)
This study was conducted to determine the effect of student learning outcomes in class XI Science 3 as the experimental class using the Problem Based Learning model and XI Science 4 as the control using the Direct Instruction learning model on the buffer solution material at SMAN 5 Model Palu. This type of research is a quasi-experimental research with a non-randomized pretest-posttest control group design. The population was student of class at XI Science 3 and at XI Science 4 at SMAN 5 Model Palu. The sampling technique used is pourposive sampling, which is one of the non-random sampling technique where the researcher determines the sampling by determining the special characteristics that are in accordance with the research objectives. The sample in this study was 26 students in the experimental class and 26 students in the control class. Testing the research data using a one-party t-test statistical analysis with prerequisite tests, namely normality, and homogeneity tests. The results of data analysis obtained in the experimental class the value of X̅1 is 75.23 with a standard deviation = 11.58 while in the control class the value of X̅2 is 68.88 with a tandard deviation = 11.07. The result of hypothesis test was tcount ≥ ttable whis is 2.08 ≥ 1.67 with a significant level (α) of 0.05 and degrees of freedom of 50. This means that Ho is rejected and H1 is accepted. So the study concludes that the Problem Based learning model has a better effect than the Direct Instruction learning model toward students learning outcomes in Buffer Solution.